P512 Results of interim analysis of a retrospective IGIBD study on adalimumab use in real practice in Italy: the REAL-life clinical effectiveness of ADAlimumab in ulcerative colitis. (25th January 2019) - Pugliese, D; Mendolaro, M; D'Incà, R; Ribaldone, D G; Principi, M; Ricci, C; Stasi, E; Scribano, M L; Bodini, G; Saibeni, S; Privitera, A C; Simondi, D; et al.
Abstract: Background: Adalimumab (ADA) is commonly use in Crohn's disease, clinical experience in ulcerative colitis (UC) is still partly limited due to later registration. Aim of this retrospective IGIBD study was to explore clinical effectiveness, safety and treatment persistence in real-world Italian patients Methods: We report here interim analyses of 218 UC patients reported by 12 Italian IBD centres, data analysis, for sake of data completeness with at least 8 weeks of follow-up after adalimumab start were carried out on 202 cases. All basal clinical characteristics were compared with the outcomes (persistency/discontinuation and safety). Univariate and multi-variate analyses were carried out Results: Median follow-up after adalimumab start was 11 months (±13), with a total of >2900 patients-months of observation. Fifty-two per cent of patients received ADA as first anti-TNF agent, full Mayo score (FMS) was moderate-to-severe (>6) in 83% cases, and co-treatment with steroids (32%) or azathioprine (17%) were present at start. Clinical effectiveness at Week 8 (at induction) was present in 170/202 (84%) cases, with median CRP drop among patients with basal CRP values >5 mg/l of 4.7 mg/l (95% CI 3–7) and median partial Mayo score (PMS) drop was 3 points. ADA was stopped in 107/202 (53%) cases before the end of the follow-up, in in 20/107 (19%) due to reasons other than clinical inadequacy (pregnancy, remission, patient choice). Within the end of the follow-up colectomy was carried out in 22 (11%) cases. Covariates associated to the risk of colectomy and of stopping ADA were basal FMS, basal active steroid treatment and week 8 PMS drop. Adverse events occurred in 24 (12%) cases, none being lethal, leading to stopping the treatment in 83% cases. Conclusions: This interim analysis support the safety and effectiveness of adalimumab in UC also in Italian real-life setting. Deeper insight will be possible with the full cohort of the study fully available.